Introduction to Data Science and Machine Learning - Sud, Keshav; Erdogmus, Pakize; Kadry, Seifedine (IntechOpen, 2020)
"Introduction to Data Science and Machine Learning" has been created with the goal to provide beginners seeking to learn about data science, data enthusiasts, and experienced data professionals with a deep understanding of data science application development using open-source programming from start to finish. This book is divided into four sections: the first section contains an introduction to the book, the second covers the field of data science, software development, and open-source based embedded hardware; the third section covers algorithms that are the decision engines for data science applications; and the final section brings together the concepts shared in the first three sections and provides several examples of data science applications.